2011
DOI: 10.1186/1477-7827-9-130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional cues on the duration of the winter anovulatory phase and on associated hormone levels in adult female Welsh pony horses (Equus caballus)

Abstract: BackgroundMares have an annual reproductive rhythm, with a phase of inactivity in midwinter. The aim of this study was to determine the impact of food restriction on physiological and metabolic hallmarks of this rhythm.MethodsOver three successive years, 3 groups of 10 mares were kept under natural photoperiod. A 'well-fed' group was fed to maintain the mares in good body condition; a 'restricted' group received a diet calculated to keep the mares thin and a 'variable' group was fed during some periods like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 76 publications
10
36
0
1
Order By: Relevance
“…Salazar-Ortiz et al [1] reported that the mean glucose concentrations of Welsh pony mares were affected by the season, which was consistent with our results. However, in contrast with the assertion of SalazarOrtiz et al [1], in the present study, the effects of both day length and gender on glucose levels suggest that glucose is an important factor for the metabolic and reproductive activity in the horse as in other species. In addition, our results suggest that elevated glucose level in the short days of the winter months is an important adaptation for winter survival under natural conditions in the horse [28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Salazar-Ortiz et al [1] reported that the mean glucose concentrations of Welsh pony mares were affected by the season, which was consistent with our results. However, in contrast with the assertion of SalazarOrtiz et al [1], in the present study, the effects of both day length and gender on glucose levels suggest that glucose is an important factor for the metabolic and reproductive activity in the horse as in other species. In addition, our results suggest that elevated glucose level in the short days of the winter months is an important adaptation for winter survival under natural conditions in the horse [28].…”
Section: Discussionsupporting
confidence: 93%
“…In the adult horse, season and nutrition are two main factors in regulation of annual reproductive activity [1]. When food availability and environmental temperature decrease during winter, physiological adaptations, including changes in reproductive and immune functions, have evolved among animals to cope with this energy restriction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algumas destas éguas podem inclusive demonstrar sinais comportamentais de estro, tais como a abertura dos membros posteriores, micção e eversão do clitóris, quando expostas ao garanhão. No entanto, éguas em boa condição corporal mantêm alguma atividade ovariana e a maioria delas apresentam ciclos estrais durante os meses de inverno (Gentry et al, 2002ab;Ferreira-Dias et al, 2005;Vecchi et al, 2010;Salazar-Ortiz et al, 2011).…”
Section: Condição Corporal E Atividade Ovarianaunclassified
“…NEFA and glucose were determined by enzymatic colorimetry on a multiparameter analyser (KONE instruments corporation, Espoo, Finland). Plasma insulin was measured by RIA from 100 ml of undiluted plasma as previously described (Salazar-Ortiz et al, 2011). All samples were analysed in a unique assay and the coefficient of variation for a sample at 1.25 ng/ml was 6%.…”
Section: Eating Behaviourmentioning
confidence: 99%